A Conceptual Framework for Creating Cartographic Representations in SDI Environments. (November 2013) - Hopfstock, Anja; Buchroithner, Manfred F; Grünreich, Dietmar
Abstract : The low awareness of the communication function of maps within the Geospatial Data Infrastructure (SDI) community has prompted PhD research (Hopfstock, 2010) to explore how the concept of user-oriented map design can be utilized to improve the SDI usability for end users. In particular, the research aimed at providing a methodology for creating effective cartographic representations and design solutions for SDI relevant user types that facilitate gaining useful Geographic Information (GI) at the interface between SDI and their users as a result of the map viewing and interpretation process. This paper outlines the empirical research and highlights the main findings.